Implementation of Oriented-Project Planning in the Development of Cultural Assets in Residency Infrastructure Writing Cultural Stories of the Pacitan Smart Community - Purnamasari, Ica; Listyaningrum, R. Anggia; Rahma, Rezka Arina; Surya, Eka Putri; Aruna, Alby; Marcelliantika, Adinda (Civiliza Publishing, 2024)
This article discusses the implementation of Oriented-Project Planning (OPP) in the development of cultural assets through a writing residency infrastructure for cultural stories in the Pacitan Cerdas Community. This community service program aims to enhance the appreciation and understanding of local culture and develop writing skills for cultural stories. The methodology includes result-oriented project planning, writing training, and intensive mentoring. The results indicate that the application of OPP significantly improves participants' writing skills and produces written works that reflect the richness of local culture. Additionally, this program strengthens community networks and promotes Pacitan culture to a broader audience. In conclusion, the implementation of OPP in cultural asset development provides a positive contribution to the preservation and promotion of local culture through the writing residency infrastructure.